Optimalisasi Peran Tenaga Pendidik dalam Meningkatkan Mutu Proses Pembelajaran di Lingkungan Sekolah Dasar (International Forum of Researchers and Lecturers, 2025)
This research aims to comprehensively explore the strategic role of educators in improving the quality of learning at the elementary school level. In the context of basic education, teachers play a central role as agents of change and the main drivers in the learning process. The main focus of this research includes three important aspects, namely the professionalism of teachers in carrying out their duties, the challenges faced in the implementation of teaching and learning activities, and optimization strategies carried out to improve the quality of learning. The research was conducted at SDN 2 Kerso, Jepara Regency, using a descriptive qualitative approach. Data collection techniques include in-depth interviews with educators and principals, direct observations in the classroom, and documentation of learning implementation plans and other supporting activities. The results of the study showed that the teachers in the school applied the practice of professionalism through work discipline, mastery of materials, pedagogical skills, and a humanist approach to students. In addition, they also use learning strategies that are adaptive, creative, and based on student needs. However, in practice, teachers face various challenges, including the diversity of student characters, low learning motivation, the influence of the family environment, limited learning facilities, and the lack of periodic training. To answer these challenges, teachers make various optimization efforts, such as participating in professional training, establishing collaboration between teachers, implementing reflective supervision, and building active communication with parents and the community. Support from school principals, committees, and social environments is also an important factor in supporting learning effectiveness. This study concludes that the improvement of the quality of learning in elementary schools is largely determined by the capacity, commitment, and ability of teachers to manage challenges creatively and professionally. With systemic support and sustainability of competency development, the role of teachers can be significantly optimized to create meaningful, effective, and sustainable learning.